To Determine Factors Causing Difficulty in Laparoscopic Donor Nephrectomy – Prospective Analytic Study - Manoj Kumar Dokania; Anshu; Peeyush Kumar; Gyan Ranjan; Nitin Agarwal; Hemant Kumar Goel; Atul Jain (Indian Journal of Transplantation)
Background: Concerns about laparoscopic donor nephrectomies exist. First and foremost, donor safety is a top priority. Second, the kidneys obtained through laparoscopic donor nephrectomy should provide recipients of kidney transplants with excellent short- and long-term renal function. This study aimed to determine the preoperative and intraoperative factors that affect the variation in the laparoscopic donor nephrectomy operative time, as well as the factors that contribute to the difficulty of the procedure. Materials and Methods: This prospective analytical study was carried out in the transplant unit over a 2-year period. The study involved all healthy adult donors scheduled for a left-sided laparoscopic nephrectomy. Another parameter used to evaluate the procedure’s results was a difficulty index. Results: A total of 33 transplant donors in all who met the requirements for inclusion were included. A laparoscopic left-sided donor nephrectomy was performed on 31 donors, while two donors underwent an open donor nephrectomy conversion. The average age of donors is 43.4 ± 5.65 years, with females outnumbering males. Males had a mean surgery duration of 163.8 min, while females had a mean of 148.4 min. The maximum patient’s body mass index ranges from 24 to 27.9 kg/m2, and the mean operating time is between 158.5 and 149.7 min. The likelihood of conversion and complications rises with the difficulty index, resulting in longer hospital stays. Conclusion: The difficulty of a laparoscopic live donor nephrectomy can be predicted by a number of factors, including sex, anatomical variance of multiple vessels, and pyelonephric adhesions, which continue to be important parameters.